Renewable Energy Cooperatives as Solution to Enhance Electrification and Economic in Developing Region - Achzab, Ade Hilmy Maulana; Putra, Iqbal Ridalta (Indonesian Journal of Energy, 2019)
Indonesia is the nation with abundant of natural resources. Natural resources itself in kind of crude oil, natural gas, coal, geothermal, hydropower, wind, and biomass become the commodity which is targeted to enhance economic development by utilizing them as the object for electrical supply in Indonesia, especially for nation electricity need. In Indonesia, the index for electrification reaches up to 94.91% in 2017 and continuously increasing year by year. It is contrary to regional electrification index as some developing region still far below 80%, even though those region have a huge amount of renewable resources potential, ranging from, solar, water, biomass, wind, geothermal as well as garbage. That potential does not go in line with renewable energy power plant which counts to 1% of total energy source. It can be analyzed that it happen because the inavailability of technology and social-political activity in Indonesia. Other than that, the system of centralization of electrical provision inhibit the potential of each region that could directly handled by local society. Therefore in this paper we propose a solution in form of renewable energy cooperatives (REC). REC applies the system of people economy to enhance the power plant establishment. REC would give capital to local society that comes from their own, to establish their own power plant. This allows the shifting to decentralization to optimize region potential and help government to reach the goal of electrification in Indonesia and plays major role in transforming Indonesian economic.